Development of Artificial Intelligence-Based Digital Video Media with the Addie Model for Intrinsic Elements of Short Stories - Mariyah, Siti; Gunawan, Wawan; Nurjati, Nunung (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The aim of this development is to produce a digital video learning media based on Artificial Intelligence for the intrinsic elements of short stories so that students can easily understand the material and learning is more interesting. In this development research, the development of short story learning media in the form of text into digital video was produced. The development of this learning media uses various Artificial Intelligence applications, namely ChatGBT, Google Docs, Leonardo, ElevenLabs, Capcut, and Canva. Artificial Intelligence-Based Digital Video Media with ADDIE Model for Intrinsic Elements of Short Stories has been refined based on expert validation data analysis and trial data analysis. The aspect that was improved was the development of animation by adding material explanations and adding questions according to the learning objectives placed in the close scene.Based on the results of the assessment given by material experts, design experts, and media experts on Artificial Intelligence-Based Digital Video Media with the ADDIE Model for the Intrinsic Elements of Short Stories, it is very feasible, meaning that the Development of Artificial Intelligence-Based Digital Video Media with the ADDIE Model for Intrinsic Elements of Short Stories has great potential to be applied in Indonesian learning, especially for the intrinsic elements of short stories. Based on the results of the assessment of the Artificial Intelligence-Based Digital Video Media trial with the ADDIE Model for the Intrinsic Elements of Short Stories given to Al-Islam Krian High School students, it means that this media is very feasible to be widely used in Indonesian language learning at the secondary education level.